Demand and growth regimes in finance-dominated capitalism and the role of the macroeconomic policy regime: a post-Keynesian comparative study on France, Germany, Italy and Spain before and after the Great Financial Crisis and the Great Recession - Eckhard Hein; Judith Martschin (Review of Evolutionary Political Economy, 2021)
We contribute to the recent debates on demand and growth regimes in modern finance-dominated capitalism linking them to the post-Keynesian research on macroeconomic policy regimes. We examine the demand and growth regimes, as well as the macroeconomic policy regimes for the big four Eurozone countries, France, Germany, Italy and Spain, for the periods 2001–2009 and 2010–2019. First, our approach supports the usefulness of the identification of demand and growth regimes according to growth contributions of the main demand components and financial balances of the macroeconomic sectors. This allows for an understanding of the demand sources of growth, or stagnation, if there is a lack of demand, of how these sources are financed and of potential financial instabilities and fragilities. Second, when it comes to the macroeconomic policy drivers of demand and growth regimes, as well as their respective changes, we show that the exclusive focus on fiscal policies, as in the previous literature, is too limited and that it is the macroeconomic policy regime which matters here, i.e. the combination of monetary, fiscal and wage policies, as well as the open economy conditions.
Keywords: E11; E12; E61; E63; E65; O57; 320; Demand and growth regimes; Macroeconomic policy regimes; Post-Keynesian macroeconomics